If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -2a = 3a Solving 7 + -2a = 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. 7 + -2a + -3a = 3a + -3a Combine like terms: -2a + -3a = -5a 7 + -5a = 3a + -3a Combine like terms: 3a + -3a = 0 7 + -5a = 0 Add '-7' to each side of the equation. 7 + -7 + -5a = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -5a = 0 + -7 -5a = 0 + -7 Combine like terms: 0 + -7 = -7 -5a = -7 Divide each side by '-5'. a = 1.4 Simplifying a = 1.4
| -7/9k=1/18-7/18 | | 0.6(3x-17)=(32-4x) | | (3x+5)*8=a | | -2x-6(42)=32 | | r+6=45 | | 4w-5=43 | | 7v-5=4-2v | | -5+7-4(-5)=(-8) | | 3y-11.5=-48.5 | | 5d-6+6=24 | | A^2+b^2-c^2=0 | | -5f+28=-21 | | a=1/x-1/y | | 4z+3=19-4z | | 3x+5+2x=2x+20 | | 6x+3(-2x+4)=8 | | (6-4)180=360 | | 2(x+4)=6r | | 2n^2=7-2n | | 80=4x-40 | | 9b^2+6-3b-3-1b= | | 8(-2+3k)=-88 | | xya=y-x | | Q=k-c/x | | Log(1-x)-log(4+x)=1 | | -v/22 | | 4z+3=19-z | | -3(2+x)=6+2(x+1) | | 3x=7x-23 | | g(x)=2+6 | | 3x+12+2x+17=119 | | 5x+7=4x+15 |